Identifying Factors Contributing to Dropouts in a Pilot Telenutrition Weight-Loss Program: A Qualitative Study - Noura M. S. Eid; Noor A. Hakim; Najlaa M. Jawad; Sarah N. Alsharif; Soaad Alsulami; Khulud A. Almalki; Dana S. Aljohani (Telemedicine Reports)
Background: Telehealth programs exhibit strong potential to improve health measures and quality of life among obese and overweight individuals for whom medical nutritional therapy remains a challenge due to poor adherence and dietary compliance. Supporting weight-management programs with dietary interventions or “telenutrition” and integrating telemonitoring and/or telehealth coaching have had a significant positive impact on weight-loss patients achieving their goals in long-term interventions. Methods: The aim of the current study was to identify the factors leading patients to drop out of a telenutrition weight-loss program, including weekly telemonitoring (total of 36 weeks) and monthly telehealth coaching (total of 6 months). Descriptive qualitative semistructured interviews were held with 10 obese and overweight participants. The data gathered through these interviews were then thematically analyzed through a content analysis. Results: The findings showed that 50% of participants who dropped out of the study felt pressured at work and/or university. Specifically, 60% reported being influenced by marital responsibilities, and 50% indicated that they did not achieve their goals. Nevertheless, participants who dropped out of the study reported that they were not negatively influenced by family factors and/or financial status. Participants also indicated feeling happy to take part in the program and noted that the diet positively influenced their psychological status. Participants also noted the clarity of instructions and that they were fully motivated during the trial. Conclusions: The factors associated with dropouts in this study were different from those identified in the literature, given that our weight-loss program was delivered remotely and supported with weekly telemonitoring and monthly telehealth coaching. Despite the dropouts, the interview data highlighted positive factors that could enhance adherence to the dietary program and reduce dropout rates in larger and longer interventions. Future research should highlight the need to develop clear guidelines related to telenutrition programs or other digital health interventions to ensure successful long-term positive outcomes.